The glideslope axes radiation propagation paths atmospheric distortion for the ground controlled approach systems - G. S. Nakhmanson; D. V. Buchnev; A. V. Suslin (Известия высших учебных заведений России: Радиоэлектроника)
The glideslope axes radiation propagation paths distortion for the ground controlled approach systems is considered. The radiation propagation tracing analytical expressions are derived. Radiation propagation paths and probability distribution densities of their angular deviations from the rated glideslope angles for different distances are calculated on the radiosonde measurements data. The confidence intervals of the propagation paths angular deviations with respect to the glideslope line for specific confidence probabilities are evaluated.